Surface and bulk modifications of amphibole asbestos in mimicked gamble's solution at acidic PH - Alessandro Pacella (Nature Portfolio, 2021)
Abstract This study aimed at investigating the surface modifications occurring on amphibole asbestos (crocidolite and tremolite) during leaching in a mimicked Gamble’s solution at pH of 4.5 and T = 37 °C, from 1 h up to 720 h. Results showed that the fibre dissolution starts with the release of cations prevalently allocated at the various M- and (eventually) A-sites of the amphibole structure (incongruent dissolution). The amount of released silicon, normalized to fibre surface area, highlighted a leaching faster for the crocidolite sample, about twenty times higher than that of tremolite. Besides, the fast alteration of crocidolite promotes the occurrence of Fe centres in proximity of the fibre surface, or possibly even exposed, particularly in the form of Fe(II), of which the bulk is enriched with respect to the oxidized surface. Conversely, for tremolite fibres the very slow fibre dissolution prevents the underlying cations of the bulk to be exposed on the mineral surface, and the iron oxidation, faster than the leaching process, significantly depletes the surface Fe(II) centres initially present. Results of this work may contribute to unravel possible correlations between surface properties of amphibole asbestos and its long-term toxicity.